Cadernos, livros, processos e uma proposta experimental sobre as formas de (apresent)ação - Almozara, Paula (Farol, 2023)
The article is a reflection of the poetic processes that use notebooks and books and are established in programmatic and systemic relationships, not only as operational and procedural phases of study for artistic projects, but seen as final establishments of production. For this, personal experiences were presented, authorial and case studies are part of this narrative that emphasizes the challenges faced and those that are currently posed for artistic production.